2007
DOI: 10.1002/art.22743
|View full text |Cite
|
Sign up to set email alerts
|

Arginine mutation alters binding of a human monoclonal antibody to antigens linked to systemic lupus erythematosus and the antiphospholipid syndrome

Abstract: Objective. Previous studies have shown the importance of somatic mutations and arginine residues in the complementarity-determining regions (CDRs) of pathogenic anti-double-stranded DNA (anti-dsDNA) antibodies in human and murine lupus, and in studies of murine antibodies, a role of mutations at position 53 in V H CDR2 has been demonstrated. We previously demonstrated in vitro expression and mutagenesis of the human IgG1 monoclonal antibody B3. The present study was undertaken to investigate, using this expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Only four human IgG anti-dsDNA antibodies from patients with SLE have been analyzed previously and all of these also fail to bind DNA in the germline configuration (7)(8)(9). Since the number of sequenced dsDNA-binding antibodies derived from lupus patients is still very limited compared with those isolated from different autoimmune mouse models, it remains a question whether conclusions drawn from murine models can be applied fully to the human dsDNAantibody repertoire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four human IgG anti-dsDNA antibodies from patients with SLE have been analyzed previously and all of these also fail to bind DNA in the germline configuration (7)(8)(9). Since the number of sequenced dsDNA-binding antibodies derived from lupus patients is still very limited compared with those isolated from different autoimmune mouse models, it remains a question whether conclusions drawn from murine models can be applied fully to the human dsDNAantibody repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…Whether nucleosomes, DNA, or phospholipid antigens released by apoptotic cells, or alternatively, foreign antigens trigger the response is unclear. Back mutation of four human IgG anti-DNA antibodies derived from lupus patients demonstrates that in their germline configuration these antibodies may fail to bind DNA (7)(8)(9). This observation would suggest that polyclonal activation is not the mechanism for the generation of pathogenic autoantibodies and that self-DNA is a critical eliciting antigen.…”
Section: Introductionmentioning
confidence: 99%
“…On the day of the experiment, wells were treated for 4 h at 37°C with 500 g/ml test monoclonal IgG or a control monoclonal IgG (a recombinant mAb with no binding to a number of Ags, previously described in Ref. 31), which lacked aPL reactivity (0 GPLU), or treated with 3 g/ml LPS (Sigma-Aldrich). Cells were then harvested with trypsin-EDTA and centrifuged at 100 ϫ g for 5 min, then incubated for 30 min at 4°C with mouse anti-human mAbs against E-selectin, VCAM-1, ICAM-1, and tissue factor (BD Biosciences).…”
Section: Measurement Of Apl-induced Ec Activation In Vitro By Facs Anmentioning
confidence: 99%
“…74 These studies are relevant to the work described above with IS4, because B3 has cross-reactivity with CL and β 2 GPI. We found that a single change (germline reversion) from Arg to Ser in B3VHCDR2 caused a dramatic Table 1 Overall binding characteristics of the 14 heavy/light chain combinations…”
Section: Results From In Vitro Expression Of Aplmentioning
confidence: 98%